Vision checking system for labelling inspection - Mariati, Sabah (2010)
This project is to present the efficient vision checking system for labeling inspection. But in this daily life, most of the factory and production produces a lot of product with error on the labeling due to the human inspection. In this project, the system is to detect the labeling error due to the printing problem. The method being used in this project is a digital image processing which is Image Subtraction Operation. The picture was processing by converting an original picture, obtained by taking a photograph of the good product and also the reject one into the gray scale format. The simulation of this inspection will be done by using the Matlab software. The system will judge a pass or rejection of the inspection target sample based on the generated inspection picture and the statistical value of the subtraction image. From the analysis of the results it shows that there are 50 original images and 50 defect images. Then, the system can be categories as an efficient system